2013
DOI: 10.1088/0953-8984/25/23/235603
|View full text |Cite
|
Sign up to set email alerts
|

High temperature far-infrared dynamics of orthorhombic NdMnO3: emissivity and reflectivity

Abstract: We report on near normal far-and mid-infrared emission and reflectivity of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 29 publications
(83 reference statements)
4
23
0
Order By: Relevance
“…Very recently, we found that those bands match our lower frequency reflectivity for RMnO 3 (R=Rare Earth) [36]. Accordingly, here we propose that in The dielectric function, ε (ω), [37] above ~T N~TC is then given by…”
Section: Ii) Far Infrared Reflectivitysupporting
confidence: 74%
“…Very recently, we found that those bands match our lower frequency reflectivity for RMnO 3 (R=Rare Earth) [36]. Accordingly, here we propose that in The dielectric function, ε (ω), [37] above ~T N~TC is then given by…”
Section: Ii) Far Infrared Reflectivitysupporting
confidence: 74%
“…Then its use in calculating the sample temperature (eq (1)) is not reliable as for temperature reading. [20]. As it is shown in fig.…”
Section: I)mentioning
confidence: 81%
“…Recently discussed for NdMnO 3 , [20] that environment trails its origin to the orbital disordered primordial perovskite lattice in which background e g electrons are in fluctuating d-orbitals [34,35]. The consequence of orbital electron dynamics in hybridized oxygen-manganese distorted e g orbitals implies embedded minute orbital misalignments.…”
Section: Iv) Thz Hybrid Soft Modesmentioning
confidence: 98%
See 1 more Smart Citation
“…Existing studies on the family of manganites perovskites, RMnO 3 as a parent of mixed valence perovskites, where R is made up of rare earth elements, such as La, Pr and Nd, were found a few decades ago due to their exotic behavior in electrical and magnetic properties [1,2]. Manganites perovskites were the favorite amongst researchers compared with other families of oxides because of their various possible substitutions that may change their crystal structure and properties [3].…”
Section: Introductionmentioning
confidence: 99%